Micro credit as a mechanism for the financial uplifment of women in chittoor district - V, Lava Kumar; P, Kesavulu (Journal of Management and Science, 2021)
The main objective of this paper is to find the impact of Micro Credit on the Empowerment of Women in Chittoor District.This paper includes many challenges that are faced by the rural women for empowering their livelihood. One of the tools that help the women in rural areas for their empowerment is Micro Credit. The Microfinance Sector occupies a position of importance in the Indian Economy. One of the major barriers to lend women is the collateral requirement. Property owning can be factually or legally difficult for women. Other major obstacles, namely, the lack of initial capital resulting from their low level of livelihoods, patriarchal control over financial decisions, the lack of entrepreneurship, market knowledge, management, and technical skills, and the lack of time resulted from the household responsibilities prevent for women in establishing an enterprise and starting economic activities.